Stress Analysis of Elevator Chain Pin in PT. Semen Padang - Rozi Saferi; Karnova Yanel; Hamdani Akmal (Jurnal Teknik Mesin, 2023)
The chain pin on the elevator chain is the most important component in the chain in transmission system which function as an axle on the chain. Chain pin is the part that is in direct contact with the sprocket teeth. This analysis aims to determine the stress that occurs in the chain pin by calculating the stress and using the autodesk inventor software. Data collection is done by measuring the dimensions of the elevator chain, the calculating the chain pin analysis using equation according to theory and using autodesk inventor for better analysis result. The result of the stress analysis on the chain pin with a diameter of 23 mm are 16.93 MPa while the result of the analysis using autodesk inventor software are 1.43 MPa. So that the stress resulting from the two analysis does not exceed the maximum allowable stress of 568.78 MPa.